KEY TENDENCIES IN SCIENTIFIC AND TECHNICAL (INNOVATIVE) ACTIVITIES OF RUSSIAN INDUSTRIAL COMPANIES - K. B. Dobrova (Модернизация, инновация, развитие, 2016)
The article off ers the analysis of expenditures on technological innovation in Russia and abroad. The author outlines the main reasons of the low level of technological development of Russian industrial companies. A number of organizational and economic measures to create conditions for technological development of the Russian economy are considered. In recent years, there was an essential increase in output of innovative products, works and services that coincided with the increased ratio of volumes of technological innovations to their costs. However, the expected decrease of this ratio in the coming years may cause slower growth of volumes of innovative production that requires drastic measures, especially aimed at restricting key factors impeding innovative activities. These factors include lack of own funds, high cost of innovations, lack of fi nancial support from the state, high economic risk and low innovative potential of the organization.